Evaluation of game performance in elite male sitting volleyball players - Molik, B.; Morgulec-Adamowicz, N.; Marszalek, J.; Kosmol, A.; Rutkowska, A.; Jakubicka, A.; Kaliszewska, E.; Kozlowski, R.; Kurowska, M.; Ploch, E.; Mustafins, P.; Gómez, M.-A. (Adapted Physical Activity Quarterly, 2017)
The aims of the current study were (a) to analyze the differences in game performances of sitting volleyball athletes representing the different types of disabilities and (b) to assess whether the seated position vertical reach is one of the crucial factors in the game performance level of sitting volleyball athletes. One hundred male athletes from various national teams participating in the European Championships in Sitting Volleyball (2009) took part in this study. The athletes were categorized according to type of disability and the results of the vertical reach in a seated position. Thirtysix games were analyzed using the Game Performance Sheet for Sitting Volleyball. Twenty-three game performance parameters were studied. In addition, the sum and effectiveness of attacks, blocks, block services, services, ball receiving, and defensive actions were calculated. The main results indicated significant differences between athletes with minimal disability and athletes with single amputations from above the knee in the level of defensive performances and the summation of defensive actions. There was also a significant difference between athletes in relation to their vertical reach during activity and attacking actions, blocks, and ball receiving. In addition, there were strong relationships between the players` vertical reach scores and their activity and effectiveness in sitting volleyball. In conclusion, the accuracy of the World Organization Volleyball for Disabled classification systems for sitting volleyball players was confirmed. There is a strong relationship between players` vertical reach and their effectiveness in sitting volleyball.